2019
DOI: 10.1111/mmi.14197
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal dTDP‐L‐rhamnose biosynthesis enzymes: functional characterization and lead compound identification

Abstract: Summary Biosynthesis of the nucleotide sugar precursor dTDP‐L‐rhamnose is critical for the viability and virulence of many human pathogenic bacteria, including Streptococcus pyogenes (Group A Streptococcus ; GAS), Streptococcus mutans and Mycobacterium tuberculosis . Streptococcal pathogens require dTDP‐L‐rhamnose for the production of structurally similar rhamnose polysaccharides in their cell wall. Via hete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 54 publications
0
33
0
1
Order By: Relevance
“…L-rhamnose biosynthetic pathways are also essential in S. pyogenes [38] and Mycobacterium smegmatis [39]. Several of these genes have, however, been mutated in S. mutans, including rmlBC [40], rmlD [38], rgpE [30,41], rgpF [41,42], and rgpG [43]. Inconsistencies between our observations and others could be related to the nature of our Tn-seq selection and/or the presence of undetected suppressor mutations that bypass essentiality in strains that carry RGP gene deletions in other studies.…”
Section: L-rhamnose Glycopolymers Are Critical For S Mutans Cell DIVmentioning
confidence: 99%
“…L-rhamnose biosynthetic pathways are also essential in S. pyogenes [38] and Mycobacterium smegmatis [39]. Several of these genes have, however, been mutated in S. mutans, including rmlBC [40], rmlD [38], rgpE [30,41], rgpF [41,42], and rgpG [43]. Inconsistencies between our observations and others could be related to the nature of our Tn-seq selection and/or the presence of undetected suppressor mutations that bypass essentiality in strains that carry RGP gene deletions in other studies.…”
Section: L-rhamnose Glycopolymers Are Critical For S Mutans Cell DIVmentioning
confidence: 99%
“…We have shown that a complete loss of the RGP structure has significant consequences for the organism in nearly all aspects required for pathogenesis in the oral cavity and potential to cause disease. The rhamnose biosynthesis pathway is an attractive antimicrobial target (50) and an alternative to targeting the machinery involved in cell wall polysaccharide synthesis. Rhamnose biosynthesis, as a target, might also be extended to life-threatening streptococcal species.…”
Section: Figmentioning
confidence: 99%
“…This is because RmlA is an enzyme in the TDP-L-rhamnose pathway. TDP-L-rhamnose is used for the synthesis of cell wall carbohydrates (24)(25)(26) and for the decoration of WTA in L. monocytogenes (27,28). Therefore, we extracted WTA from the sigB and rsbU mutants and compared the apparent molecular mass with the WTA extracted from the rmlA mutant.…”
Section: S2cmentioning
confidence: 99%